Chlorhexidine gluconate usage is associated with antiseptic tolerance in staphylococci from the neonatal intensive care unit. Issue 4 (17th November 2021) - Sethi, Dheeraj K; Felgate, Heather; Diaz, Maria; Faust, Kirstin; Kiy, Cemsid; Clarke, Paul; Härtel, Christoph; Rupp, Jan; Webber, Mark A
Abstract: Background: Intravascular catheters are essential for care in Neonatal Intensive Care Units (NICUs) but predispose infants to catheter-associated infections including late-onset sepsis, commonly caused by CoNS. Antiseptics are applied to prevent infection with chlorhexidine (CHG) and octenidine (OCT) the most common agents used. Objectives: To investigate the association between antiseptic use and bacterial susceptibility. Methods: CoNS isolates were collected from two NICUs with differing antiseptic regimens: Norwich, UK (using CHG) and Lubeck, Germany (using OCT). CoNS were isolated from different body sites of babies upon admission, and weekly thereafter. Antiseptic susceptibility testing was performed, and a selection underwent genome sequencing. Results: A total of 1274 isolates were collected. UK isolates ( n =  863) were significantly less susceptible than German isolates ( n =  411) to both CHG (mean MIC: 20.1 mg/L versus 8.9 mg/L) and OCT (mean MIC: 2.3 mg/L versus 1.6 mg/L). UK isolates taken on admission were more susceptible to CHG than subsequent isolates. No cross-resistance between the agents was seen. Genome sequencing of 122 CoNS showed the most common species to be Staphylococcus epidermidis and Staphylococcus haemolyticus and phylogenetic analysis suggested antiseptic tolerance evolved multiple times in independent lineages. There was no evidence of dominant antiseptic tolerant clones and carriage of genes previously implicated in antimicrobial susceptibility ( qac, smr, norA / B ), did not correlate with CHG or OCT susceptibility. Conclusions: Long-term CHG use may select for CHG and OCT tolerance in CoNS. This highlights the different potential for separate antiseptic regimens to select for resistance development. This could be an important factor in developing future infection control policies.